Degradation of 2,4-dichlorophenoxyacetic acid by Pseudomonas cepacia DBO1(pRO101) in a dual-substrate chemostat. - Daugherty, D D (1994)
To determine the effect of a secondary carbon source on biodegradation of a chloroaromatic compound, Pseudomonas cepacia DBO1(pRO101) was grown in continuous cultures on basal salts media containing various mixtures of 2,4-dichlorophenoxyacetic acid (2,4-D) and succinate. Both succinate and 2,4-D were metabolized over the entire range of dilution rates and compositions analyzed (0.05 to 0.6 h-1). 2,4-Dichlorophenol (DCP), the only intermediate detected, accumulated to significant amounts (10 to 21 mg/liter) in the chemostat only when the dilution rate was 0.4 h-1 or greater. At these concentrations, DCP reduced the apparent growth rate of P. cepacia DBO1(pRO101) in batch cultures by 15 to 35% over the apparent growth rate on succinate alone. Succinate fed to the chemostat increased the cell density as well as the percentage of 2,4-D that was consumed at each dilution rate. When the amount of succinate in the feed exceeded the amount of 2,4-D, the specific rates of 2,4-D degradation in the chemostat or by washed cells were significantly lower than the specific rates for cells grown on 2,4-D alone, suggesting repression by succinate. However, when the amount of 2,4-D in the feed exceeded the amount of succinate, the specific rates of 2,4-D degradation remained at values equivalent to or higher than the specific rate for cells grown on 2,4-D alone. DCP accumulated significantly in the washed-cell assay, suggesting that the level of DCP hydroxylase is rate limiting.(ABSTRACT TRUNCATED AT 250 WORDS)